Anesthetic Management for Sternotomy in a Patient with Anterior Mediastinal Tumor: A Case Report - Kurniawan, Arfian Pascalis; Rusli, Joseph; Hapdijaya, Indra; Gunadi, Julia Windi (JAI (Jurnal Anestesiologi Indonesia), 2021)
Background: Anterior mediastinal masses (AMMs) pose significant anesthetic challenges, risking airway obstruction, cardiovascular collapse, and hemodynamic instability, especially in the supine position. Preoperative assessment, including imaging and cardiopulmonary evaluation, is crucial. Anesthetic management prioritizes spontaneous ventilation (SV), airway patency, and hemodynamic stability, often employing awake intubation, inhalational induction, and neuromuscular blockade avoidance. A multidisciplinary, individualized anesthetic management of the sternotomy approach optimizes outcomes.Case: 50-year-old male with anterior mediastinal tumor (AMT) scheduled for elective sternotomy. The patient experienced chest pain and a persistent cough with displacement and indentation of the aorta and inferior vena cava as observed on contrast-enhanced computed tomography (CT) scan, indicating high surgical risk. Anesthesia induction involved fentanyl, midazolam, atracurium, and propofol, followed by intubation with a left-sided double-lumen tube (DLT) for one-lung ventilation.Discussion: Mediastinal masses pose significant anesthetic risks, primarily due to the potential for mediastinal mass syndrome (MMS). Preoperative imaging and symptom-based risk stratification are critical. Anesthetic goals include maintaining SV and avoiding neuromuscular blockade when possible, as loss of SV is often linked to MMS onset. However, in procedures like sternotomy requiring deep anesthesia and muscle relaxation, airway control may necessitate neuromuscular agents. In such cases, preparedness for difficult ventilation is essential. We utilized a left-sided DLT to facilitate one-lung ventilation and surgical access. Postoperative intensive care unit (ICU) monitoring is advised for high-risk patients.Conclusion: This case's importance lies in the complex anesthetic management of sternotomy for anterior mediastinal mass resection, requiring meticulous planning to prevent airway and cardiovascular compromise. A multidisciplinary approach and early diagnosis are key to optimizing patient safety and outcomes.